Re-utilizing Space: Accommodating Tourists in Homestay Houses in Northern Thailand - Oranratmanee, Rawiwan (Journal of Architectural/Planning Research and Studies (JARS), 2018)
This paper discusses the way in which rural houses in Northern Thailand are adapted to meet emerging demand for tourist accommodation in a private ‘homestay’. It is based on qualitative fieldwork in three homestay villages in Northern Thailand. The research combines the studies of vernacular tradition, tourism and ‘home’ in order to explain the changes in homestays by analyzing the interrelationships between space use, social interaction and the meaning of home and homestay. The findings reveal that the norms concerning guest space, patterns of life and the perceived meaning of home in the Northern Thai context play significant roles in adjusting the lives and outlooks of residents, as well as their space, to homestays. While this has positive implications in terms of re-using space to supplement the family income, homestays also bring about profound shifts in the moral values and meanings of home. The research differs from other home and homestay studies as it bridges the three fields of architecture, tourism and the study of home. It thereby contributes to our understanding of transformation and continuity within a vernacular environment and tradition undergoing significant internal and external forces of change.